The effect of the choice of screening test when measuring the prevalence of gambling disorder: A cross-sectional study in Japan - Tatsuya Noda; Moritoshi Kido; Chieko Ito; Toshiyuki Ojima (PLoS ONE, 2025)
This study examines the influence of the selection of screening tests and cut-off scores on the prevalence of gambling disorders by simultaneously administering several tests to the same sample. The survey was conducted online in 2021, with 2,000 respondents distributed equally across two prefectures in Japan. Four screening tests were administered simultaneously: the South Oaks Gambling Screen (SOGS), Problem Gambling Severity Index (PGSI), Lie/Bet questionnaire, and Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5). The prevalence at the original cut-off scores was markedly different, with the SOGS (10.3%) showing the highest prevalence and the DSM-5 (3.8%) showing the lowest prevalence. Adjusting the cut-off score from 5 to 4 for the SOGS increased prevalence by 2.9%, while changing the PGSI cut-off score from 8 to 7 only increased it by 0.5%. This is the first study in Japan to simultaneously compare the scores for multiple screening tests and cut-off scores regarding gambling disorders. The SOGS screens more individuals with a possible gambling disorder than other measures, and altering the cut-off score significantly affected its prevalence. Selecting appropriate screening tests and cut-off scores is crucial to accurately assessing the prevalence of possible gambling disorders.